Android Application to Control Commercial UAV - P, Vishva; V, Nivethitha P; V, Sowndarya Lakshmi; S, Vithun S; G, Manavaalan (Journal of Ubiquitous Computing and Communication Technologies, 2023)
Unmanned Aerial Vehicles (UAVs) have been used in many industries because they can fly out of sight, maximize production, reduce costs and risks, while ensuring visual security and safety for human workers during pandemics. A commercial drone is typically controlled and navigated using a remote control and a mobile application. Mobile apps are used to visualize the drone’s coordinates on a map. There is no direct mobile app for controlling a developer drone like the DJI Matrice 100. This research presents a mobile application for controlling a DJI drone as well as a sensor system for providing information about obstacles encountered during the flight.